The emerald city of oz ebook The emerald city of oz. - Shanower, Eric (The Emerald City of Oz (2013)., 2014)
Collects Emerald City of Oz #1-5. Uncle Henry can't pay the mortgage, so he, Aunt Em and Dorothy must leave their Kansas home. Where can they go? To the Land of Oz, of course! Dorothy and the Wizard take Em and Henry on a grand tour, discovering knowledge pills and living paper dolls, solving living puzzles, suffering abuse from living kitchen utensils and drooling over living baked goods - but will anyone in Oz be left living after the Nomes attack, allied with the highly disagreeable Growleywogs?